Wear-resistant phase change energy storage material and preparation method thereof
By using CeO2-ZrO2 mixture, modified Elosite nanotubes and titanium carbide in phase change energy storage materials, and using a combination of hydrothermal and microwave methods, the problem of insufficient wear resistance of existing phase change energy storage materials is solved, achieving a longer service life and better reliability.
Patent Information
- Application Number
- CN202411787382.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing phase change energy storage materials are prone to deterioration and failure due to wear during long-term use, and lack wear resistance.
Wear-resistant phase change energy storage materials are prepared by combining hydrothermal method and microwave method using materials such as CeO2-ZrO2 mixture, modified Elosite nanotubes and titanium carbide. The method includes dissolving zirconium nitrate and cerium nitrate, adding hydrazine hydrate and diethanolamine for hydrothermal treatment, then roasting in a high-purity oxygen atmosphere, and grinding in a ball mill, and finally obtaining the energy storage material by sintering molding.
The prepared wear-resistant phase change energy storage materials show good wear resistance in physical properties, extending service life and improving reliability, while improving the overall hardness and energy storage capacity of the material.
Smart Images

Figure BDA0005174404600000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage materials and relates to a wear-resistant phase-change energy storage material and a preparation method thereof. Background Art
[0002] Phase change material is a material with special properties that can change physical properties when the temperature or pressure changes. This material can change from one solid phase to another solid phase, or from one liquid phase to another liquid phase, or even change to a gas phase. Phase change materials have reversible phase change characteristics and can absorb or release a large amount of heat energy during the phase change process. Therefore, they are widely used in energy storage, temperature control and other fields.
[0003] Wear-resistant phase change energy storage materials not only maintain the basic properties of phase change materials, but also have excellent wear resistance. This material can maintain stable performance during long-term use and reduce performance degradation and failure caused by wear. As a new type of material with unique properties, wear-resistant phase change energy storage materials have broad application prospects in the fields of energy storage and temperature control. Summary of the invention
[0004] The purpose of the present invention is to provide a wear-resistant phase-change energy storage material and a preparation method thereof, which has the characteristics of wear resistance.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A wear-resistant phase-change energy storage material, the energy storage material formula is as follows, by mass percentage, CeO2-ZrO2 mixture 50-60%, modified halloysite nanotubes 20-30%, titanium carbide 10-15%, dispersant 2-3%, coupling agent 2-3%,
[0007] The preparation method of CeO2-ZrO2 mixture is as follows:
[0008] S1.1: Dissolve zirconium nitrate and cerium nitrate in deionized water at a molar ratio of 2:1 to obtain a solution with a metal concentration of 0.1 mol / L, and perform ultrasonic treatment for 0.5 h to obtain a mixed solution A;
[0009] S1.2: adding hydrazine hydrate to the mixed solution A, wherein the molar ratio of the added hydrazine hydrate to the metal element is 6:1, stirring at a speed of 140 r / min while adding, and continuing ultrasonication for 0.5 h after stirring to obtain a mixed solution B;
[0010] S1.3: Add 1 wt% of a mixture of diethanolamine and polyethylene glycol-2000 to solution B, continue stirring at a speed of 140 r / min to obtain a mixed solution C, transfer the mixed solution C to an autoclave with a filling degree of 80%, and perform a hydrothermal treatment at 140° C. for 12 h to obtain a mixed solution D;
[0011] S1.4: centrifuging the mixed solution D at a centrifugal speed of 2500 rpm, filtering, and drying at 80°C for 12 h to obtain a solid E;
[0012] S1.5: placing solid E in a muffle furnace and calcining it in a high-purity oxygen atmosphere for 3 hours at a temperature of 400°C. After calcination, cooling it to room temperature, grinding it in a ball mill at a speed of 300 r / min for 1 hour, and obtaining the CeO2-ZrO2 mixture;
[0013] The preparation method of modified halloysite nanotubes is as follows:
[0014] S2.1: Graphene and yttrium oxide were mixed in a mass ratio of 10:1, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture F;
[0015] S2.2: Disperse the mixture F in an ethanol solution and sonicate for 0.5 h to obtain a uniformly dispersed suspension G;
[0016] S2.3: immersing the halloysite nanotubes in the suspension G, wherein the mass ratio of the halloysite nanotubes to the mixture F is 1:1, stirring at a speed of 140 r / min for 12 h, to obtain a solid-liquid mixture H;
[0017] S2.4: The solid-liquid mixture H was heated at a microwave power of 1000 W for 30 s, and after microwave heat treatment, it was cooled to room temperature to obtain a solid I;
[0018] S2.5: The solid I is washed with deionized water at room temperature, and then dried at 80° C. for 6 h. After drying, the solid is ground to a particle size of 200 mesh to obtain the modified halloysite nanotube.
[0019] Furthermore, the dispersant is polyethylene glycol with a molecular weight of 2000-4000.
[0020] Furthermore, the coupling agent is one of vinyl triethoxy silane and vinyl tri-β-methoxyethoxy silane.
[0021] Furthermore, the solid particle size obtained by grinding in S1.5 is 150 mesh.
[0022] A method for preparing a wear-resistant phase-change energy storage material. The specific process of the method for preparing the energy storage material is as follows:
[0023] S5.1: Put the CeO2-ZrO2 mixture, modified halloysite nanotubes, titanium carbide, dispersant and coupling agent into a ball mill according to the formula ratio and grind them at a speed of 400 r / min for 2 h to obtain a mixture J;
[0024] S5.2: Place the mixture J into a mold and sinter it at 400°C for 3 hours. After sintering, purge with nitrogen and cool to room temperature to obtain the energy storage material.
[0025] Furthermore, the particle size of the mixture J obtained by grinding in S5.1 is 150 mesh.
[0026] Furthermore, the flow rate of nitrogen in S5.2 is 15 m / s.
[0027] Furthermore, in S5.2, the mixture is cooled to room temperature at a rate of 3°C / min.
[0028] In the CeO2-ZrO2 mixture prepared by the present invention, ZrO2 is tetragonal zirconium oxide. During the preparation process, zirconium nitrate and cerium nitrate are dissolved in deionized water to form a corresponding salt solution, and then hydrazine hydrate (N2H4·H2O) is added as a complexing agent to react with zirconium ions (Zr 4+ ) and cerium ions (Ce 3+ / Ce 4+ ) will form complex clusters. This complexation helps to control the hydrothermal growth process of zirconium oxide and cerium oxide, and may reduce their size. In the present invention, diethanolamine and polyethylene glycol-2000 are added as complexing aids to make the hydrothermal reaction more stable. The solution containing the complex cluster is placed in an autoclave and subjected to hydrothermal treatment at 140°C. The strong reducing property of hydrazine hydrate and the high temperature and high pressure conditions of the hydrothermal treatment jointly promote the hydrolysis reaction of the complex cluster to generate a nanoparticle mixture of tetragonal zirconium oxide and cerium oxide. The nano-sized tetragonal zirconium oxide and cerium oxide particles prepared by the hydrothermal method have a large specific surface area and interface effect, which is beneficial to the ion transport and energy conversion process in the energy storage material. Due to the size effect at the nanometer level, the tetragonal zirconium oxide and cerium oxide nanoparticles prepared by the hydrothermal method show good wear resistance in physical properties. This wear resistance makes the mixture have a longer service life and better reliability in the application of energy storage materials.
[0029] The tetragonal zirconium oxide and cerium oxide mixture prepared by the hydrothermal method is placed in high-purity oxygen for calcination, which can further stabilize its crystal structure and improve its physical and chemical properties; in addition, the high-purity oxygen environment can also help remove impurities in the mixture and improve its purity.
[0030] Tetragonal zirconia and cerium oxide are both materials with high energy density. Their mixture shows higher energy storage capacity in terms of energy storage. The addition of cerium oxide can improve the ionic conductivity of tetragonal zirconia, making the mixture have better performance in energy storage material applications. Tetragonal zirconia and cerium oxide will also produce a synergistic effect in the mixture, because the ionic radius of cerium oxide is similar to that of ZrO2. 4+ This allows the two to form a stable solid solution; and as an ion conductor, cerium oxide can improve the ionic conductivity of zirconium oxide, while zirconium oxide can improve the structural stability of the mixture, and through mutual complementation and reinforcement, the overall performance of the energy storage material is further improved.
[0031] The present invention also prepares modified halloysite nanotubes by combining impregnation and microwave methods. Graphene, as a high-performance two-dimensional material, has extremely high electrical conductivity and specific surface area. Mixing it with yttrium oxide and loading it on halloysite nanotubes can further improve its energy density, making it an excellent energy storage material; halloysite nanotubes have unique structural properties, with a high surface area, special pore structure and stable structure, all of which help to stabilize the mixture of graphene and yttrium oxide, thereby enhancing the stability of the entire energy storage system; and the loading of the mixture of graphene and yttrium oxide on halloysite nanotubes can optimize the transmission path of ions in the material and improve the ion transmission rate and efficiency.
[0032] Through the impregnation method, a mixture of graphene and yttrium oxide can be evenly loaded on halloysite nanotubes to form a stable composite material. This composite material combines the high conductivity of graphene and the stability of yttrium oxide, as well as the unique structural advantages of halloysite nanotubes. The microwave method can quickly and evenly heat the sample, allowing graphene and yttrium oxide to better combine on the halloysite nanotubes. The microwave method will form a carbon-oxygen chemical bond between graphene and yttrium oxide, thereby enhancing the bonding force between them; graphene and yttrium oxide will also react with the hydroxyl groups on the halloysite nanotubes and form stable chemical bonds, further optimizing the performance of the phase change energy storage material.
[0033] When titanium carbide is added to a phase change energy storage material, it can significantly increase the overall hardness of the material, thereby improving wear resistance. The addition of titanium carbide can strengthen the crystal structure and lattice of the phase change energy storage material and improve the mechanical properties of the material. This enhanced crystal structure helps to resist external wear and improve the wear resistance of the material. In the present invention, the CeO2-ZrO2 mixture, modified halloysite nanotubes, titanium carbide, dispersant and coupling agent are sintered by grinding and sintering to obtain the final wear-resistant phase change energy storage material.
[0034] Beneficial effects of the present invention:
[0035] The present invention adopts hydrazine hydrate and uses a hydrothermal method to prepare a mixture of tetragonal zirconium oxide and cerium oxide through complexation, and calcines it in high-purity oxygen to obtain a CeO2-ZrO2 mixture, which exhibits good wear resistance in physical properties. This wear resistance enables the mixture to have a longer service life and better reliability in energy storage material applications.
[0036] The present invention prepares modified halloysite nanotubes by combining impregnation and microwave methods. Through the impregnation method, a mixture of graphene and yttrium oxide can be uniformly loaded on the halloysite nanotubes to form a stable composite material. The microwave method can quickly and uniformly heat the sample, so that the graphene and yttrium oxide are better combined on the halloysite nanotubes and a stable chemical bond is formed between the three, thereby further optimizing the performance of the phase change energy storage material.
[0037] The present invention also introduces titanium carbide into the phase change energy storage material, which can significantly improve the overall hardness of the material, thereby improving the wear resistance. DETAILED DESCRIPTION
[0038] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0039] Formula ratio 1: CeO2-ZrO2 mixture 60%, modified halloysite nanotubes 20%, titanium carbide 15%, PEG-20002%, vinyl triethoxysilane 3%;
[0040] Formula ratio 2: CeO2-ZrO2 mixture 50%, modified halloysite nanotubes 30%, titanium carbide 15%, PEG-2000 3%, vinyl tri-β-methoxyethoxy-silane 2%;
[0041] Formula ratio 3: CeO2-ZrO2 mixture 60%, modified halloysite nanotubes 25%, titanium carbide 10%, PEG-40003%, vinyl triethoxysilane 2%;
[0042] The preparation method of CeO2-ZrO2 mixture is as follows:
[0043] S1.1: Dissolve zirconium nitrate and cerium nitrate in deionized water at a molar ratio of 2:1 to obtain a solution with a metal concentration of 0.1 mol / L, and perform ultrasonic treatment for 0.5 h to obtain a mixed solution A;
[0044] S1.2: adding hydrazine hydrate to the mixed solution A, wherein the molar ratio of the added hydrazine hydrate to the metal element is 6:1, stirring at a speed of 140 r / min while adding, and continuing ultrasonication for 0.5 h after stirring to obtain a mixed solution B;
[0045] S1.3: Add 1 wt% of a mixture of diethanolamine and polyethylene glycol-2000 to solution B, continue stirring at a speed of 140 r / min to obtain a mixed solution C, transfer the mixed solution C to an autoclave with a filling degree of 80%, and perform a hydrothermal treatment at 140° C. for 12 h to obtain a mixed solution D;
[0046] S1.4: centrifuging the mixed solution D at a centrifugal speed of 2500 rpm, filtering, and drying at 80°C for 12 h to obtain a solid E;
[0047] S1.5: The solid E is placed in a muffle furnace and calcined in a high-purity oxygen atmosphere for 3 hours at a temperature of 400°C. After calcination, the solid is cooled to room temperature and ground in a ball mill at a speed of 300 r / min for 1 hour to obtain the CeO2-ZrO2 mixture, wherein the particle size of the mixture is 150 mesh;
[0048] The preparation method of modified halloysite nanotubes is as follows:
[0049] S2.1: Graphene and yttrium oxide were mixed in a mass ratio of 10:1, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture F;
[0050] S2.2: Disperse the mixture F in an ethanol solution and sonicate for 0.5 h to obtain a uniformly dispersed suspension G;
[0051] S2.3: immersing the halloysite nanotubes in the suspension G, wherein the mass ratio of the halloysite nanotubes to the mixture F is 1:1, stirring at a speed of 140 r / min for 12 h, to obtain a solid-liquid mixture H;
[0052] S2.4: The solid-liquid mixture H was heated at a microwave power of 1000 W for 30 s, and after microwave heat treatment, it was cooled to room temperature to obtain a solid I;
[0053] S2.5: The solid I is washed with deionized water at room temperature, and then dried at 80° C. for 6 h. After drying, the solid is ground to a particle size of 200 mesh to obtain the modified halloysite nanotube.
[0054] Example 1
[0055] S5.1: Put the CeO2-ZrO2 mixture, modified halloysite nanotubes, titanium carbide, dispersant and coupling agent into a ball mill according to the formula ratio 1 for grinding, the ball mill speed is 400r / min, the grinding time is 2h, and a mixture J is obtained, and the particle size of the mixture J is 150 mesh;
[0056] S5.2: Place the mixture J into a mold and sinter it at 400°C for 3 hours. After sintering, use nitrogen to purge with a nitrogen flow rate of 15m / s. Cool it to room temperature at a rate of 3°C / to obtain the energy storage material.
[0057] Example 2
[0058] S5.1: Put the CeO2-ZrO2 mixture, modified halloysite nanotubes, titanium carbide, dispersant and coupling agent into a ball mill according to the formula ratio 2 for grinding, the ball mill speed is 400r / min, the grinding time is 2h, and a mixture J is obtained, and the particle size of the mixture J is 150 mesh;
[0059] S5.2: Place the mixture J into a mold and sinter it at 400°C for 3 hours. After sintering, use nitrogen to purge with a nitrogen flow rate of 15m / s. Cool it to room temperature at a rate of 3°C / to obtain the energy storage material.
[0060] Example 3
[0061] S5.1: Put the CeO2-ZrO2 mixture, modified halloysite nanotubes, titanium carbide, dispersant and coupling agent into a ball mill according to the formula ratio 3 for grinding, the ball mill speed is 400r / min, the grinding time is 2h, and a mixture J is obtained, and the particle size of the mixture J is 150 mesh;
[0062] S5.2: Place the mixture J into a mold and sinter it at 400°C for 3 hours. After sintering, use nitrogen to purge with a nitrogen flow rate of 15m / s. Cool it to room temperature at a rate of 3°C / to obtain the energy storage material.
[0063] Comparative Example 1
[0064] In this comparative example, the prepared CeO2-ZrO2 mixture is not used, only ZrO2 is used, and the remaining steps are consistent with Example 1.
[0065] Comparative Example 2
[0066] In this comparative example, high-purity oxygen is not used to calcine the CeO2-ZrO2 mixture, and the remaining steps are consistent with those in Example 1.
[0067] Comparative Example 3
[0068] In this comparative example, modified halloysite nanotubes are not used, only ordinary halloysite nanotubes are used, and the remaining steps are consistent with those in Example 1.
[0069] Comparative Example 4
[0070] In this comparative example, yttrium oxide was not added to the modified halloysite nanotubes, and the remaining steps were consistent with those in Example 1.
[0071] Comparative Example 5
[0072] In this comparative example, the modified halloysite nanotubes were not treated by microwave method, and the remaining steps were consistent with those in Example 1.
[0073] Comparative Example 6
[0074] In this comparative example, titanium carbide was not added, and the remaining steps were consistent with those in Example 1.
[0075] The wear resistance of the embodiment and the comparative example was tested by using a JM IV abrasion tester and a rotating friction rubber wheel method. The wear resistance of the present invention was measured by the average value of the coating mass loss (weight loss method) after 100 grinding revolutions. The load was 10N, the rotation speed was 80r / min, the test temperature was 25°C, the relative humidity was 40%, the mass was tested to an accuracy of 0.01mg, and the average value of 3 measurements was taken as the result.
[0076] The initial thermal conductivity of the phase change energy storage material and the thermal conductivity after 100 cycles of hot and cold cycles were tested using a thermal conductivity meter for the embodiments and comparative examples.
[0077] The experimental data are summarized in the following table:
[0078]
[0079] It can be seen from the embodiments and comparative examples that the addition of CeO2-ZrO2 mixture, modified halloysite nanotubes and titanium carbide makes the prepared phase change energy storage material have better wear resistance, which can effectively improve its service life. It can also be seen from the embodiments and comparative examples that the addition of CeO2-ZrO2 mixture and modified halloysite nanotubes also improves the stability of the phase change energy storage material.
[0080] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A wear-resistant phase change energy storage material, characterized in that: The energy storage material formula is as follows: by mass percentage, CeO2-ZrO2 mixture 50-60%, modified halloysite nanotubes 20-30%, titanium carbide 10-15%, dispersant 2-3%, coupling agent 2-3%, The preparation method of CeO2-ZrO2 mixture is as follows: S1.1: Dissolve zirconium nitrate and cerium nitrate in deionized water at a molar ratio of 2:1 to obtain a solution with a metal concentration of 0.1 mol / L, and perform ultrasonic treatment for 0.5 h to obtain a mixed solution A; S1.2: adding hydrazine hydrate to the mixed solution A, wherein the molar ratio of the added hydrazine hydrate to the metal element is 6:1, stirring at a speed of 140 r / min while adding, and continuing ultrasonication for 0.5 h after stirring to obtain a mixed solution B; S1.3: Add 1 wt% of a mixture of diethanolamine and polyethylene glycol-2000 to solution B, continue stirring at a speed of 140 r / min to obtain a mixed solution C, transfer the mixed solution C to an autoclave with a filling degree of 80%, and perform a hydrothermal treatment at 140° C. for 12 h to obtain a mixed solution D; S1.4: centrifuging the mixed solution D at a centrifugal speed of 2500 rpm, filtering, and drying at 80°C for 12 h to obtain a solid E; S1.5: placing solid E in a muffle furnace and calcining it in a high-purity oxygen atmosphere for 3 hours at a temperature of 400°C. After calcination, cooling it to room temperature, grinding it in a ball mill at a speed of 300 r / min for 1 hour, and obtaining the CeO2-ZrO2 mixture; The preparation method of modified halloysite nanotubes is as follows: S2.1: Graphene and yttrium oxide were mixed in a mass ratio of 10:1, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture F; S2.2: Disperse the mixture F in an ethanol solution and sonicate for 0.5 h to obtain a uniformly dispersed suspension G; S2.3: immersing the halloysite nanotubes in the suspension G, wherein the mass ratio of the halloysite nanotubes to the mixture F is 1:1, stirring at a speed of 140 r / min for 12 h, to obtain a solid-liquid mixture H; S2.4: The solid-liquid mixture H was heated at a microwave power of 1000 W for 30 s, and after microwave heat treatment, it was cooled to room temperature to obtain a solid I; S2.5: The solid I is washed with deionized water at room temperature, and then dried at 80° C. for 6 h. After drying, the solid is ground to a particle size of 200 mesh to obtain the modified halloysite nanotube.
2. A wear-resistant phase change energy storage material according to claim 1, characterized in that: The dispersant is polyethylene glycol with a molecular weight of 2000-4000.
3. The wear-resistant phase change energy storage material according to claim 1, characterized in that: The coupling agent is one of vinyl triethoxy silane and vinyl tri-β-methoxyethoxy silane.
4. The wear-resistant phase change energy storage material according to claim 1, characterized in that: The solid particle size obtained by grinding in S1.5 is 150 mesh.
5. A method for preparing a wear-resistant phase-change energy storage material, based on a wear-resistant phase-change energy storage material according to any one of claims 1 to 4, characterized in that: The specific process of the preparation method of the energy storage material is as follows: S5.1: Put the CeO2-ZrO2 mixture, modified halloysite nanotubes, titanium carbide, dispersant and coupling agent into a ball mill according to the formula ratio and grind them at a speed of 400 r / min for 2 h to obtain a mixture J; S5.2: Place the mixture J into a mold and sinter it at 400°C for 3 hours. After sintering, purge with nitrogen and cool to room temperature to obtain the energy storage material.
6. The method for preparing a wear-resistant phase-change energy storage material according to claim 5, characterized in that: The particle size of the mixture J obtained by grinding in S5.1 is 150 mesh.
7. The method for preparing a wear-resistant phase-change energy storage material according to claim 5, characterized in that: The flow rate of nitrogen in S5.2 is 15 m / s.
8. The method for preparing a wear-resistant phase-change energy storage material according to claim 5, characterized in that: The S5.2 was cooled to room temperature at a rate of 3°C / min.
Citation Information
Patent Citations
Cerium stabilized cubic zirconia ceramic material and preparation method thereof
CN102887706A
Sizing composite phase change material based on novel nano ceramic skeleton and preparation method of sizing composite phase change material
CN115651610A
Cerium oxide / yttrium oxide composite stabilized zirconium oxide grinding medium and preparation method thereof
CN119038989A
Oxygen storage / release material and method for producing the same
US20230356192A1